Optimal antiplatelet therapy in patients at high bleeding risk undergoing complex percutaneous coronary intervention . (21st July 2022) - Ortega-Paz, Luis; Angiolillo, Dominick J
Graphical Abstract: Graphical Abstract Domains and mitigation strategies for a comprehensive evaluation and treatment of CHIP patients. Complex high-risk and indicated PCI (CHIP) represents a group of patients with an indication for revascularization but with a high or extreme surgical risk and in whom the risk of procedural complications exceeds the average risk of standard percutaneous coronary intervention (PCI). Overall, patient risk is illustrated by the three different domains, which can be overlapping and additive. The three main domain characteristics are patient, lesion, and haemodynamic status. Left panel: within each domain are listed the different elements and risks to consider when selecting, planning, performing, and follow-up CHIP patients. Right panel: mitigation strategies that may be considered for overcoming the potential pitfalls of CHIP procedures and patient issues on follow-up. Mitigation strategies are listed in the same order as their corresponding elements/risks in the right panel. *Syntax score ≥33. ASA, acetylsalicylic acid; CAD, coronary artery disease; CKD, chronic kidney disease; CTO, chronic total occlusion; DAPT, dual antiplatelet therapy; ECLA, excimer laser coronary angioplasty; GPI, glycoprotein inhibitors; HBR, high bleeding risk; IV, intravenous; IVL, intravascular lithotripsy; LM, left main; MCS, mechanical circulatory support; RHC, right heart catheterization.